Manipulation gesture effect in visual and auditory presentations: the link between tools in perceptual and motor tasks - Rey, Amandine E.; Roche, Kévin; VERSACE, Rémy; Chainay, Hanna (Frontiers in Psychology, 2015)
There is much behavioral and neurophysiological evidence in support of the idea that seeing a tool activates motor components of action related to the perceived object (e.g., grasping, use manipulation). However, the question remains as to whether the processing of the motor components associated with the tool is automatic or depends on the situation, including the task and the modality of tool presentation. The present study investigated whether the activation of motor components involved in tool use in response to the simple perception of a tool is influenced by the link between prime and target tools, as well as by the modality of presentation, in perceptual or motor tasks. To explore this issue, we manipulated the similarity of gesture involved in the use of the prime and target (identical, similar, different) with two tool presentation modalities of the presentation tool (visual or auditory) in perceptual and motor tasks. Across the experiments, we also manipulated the relevance of the prime (i.e., associated or not with the current task). The participants saw a first tool (or heard the sound it makes), which was immediately followed by a second tool on which they had to perform a perceptual task (i.e., indicate whether the second tool was identical to or different from the first tool) or a motor task (i.e., manipulate the second tool as if it were the first tool). In both tasks, the similarity between the gestures employed for the first and the second tool was manipulated (Identical, Similar or Different gestures). The results showed that responses were faster when the manipulation gestures for the two tools were identical or similar, but only in the motor task. This effect was observed irrespective of the modality of presentation of the first tool, i.e., visual or auditory. We suggest that the influence of manipulation gesture on response time depends on the relevance of the first tool in motor tasks. We discuss these motor activation results in terms of the relevance and demands of the tasks.